The Effectiveness of Reduction of Weight Metal Contents of Pb, and Hg in Water Electro-coagulation Method - Ferry Kriswandana (Journal of Global Pharma Technology, 2020)
Background and Aim: Heavy metals in certain levels can reduce the quality of air, water, and soil. Furthermore, causing health problems for plants, animals and humans, when there is accumulation as a result of industrial activity. Until now, the reduction of heavy metal content in liquid waste has been carried out physically, chemically and biologically. Therefore it is deemed necessary to reduce levels of heavy metals in liquid waste by electrocoagulation. The purpose of this study is to study the performance of electrocoaglation as a reducing agent in reducing Pb and Hg levels in water, so that it can provide references and input for the electroplating industry, batik industry, and others. Method and Materials: This research is a true experimental research with a post test only control group design, which is a research design consisting of a control group and an experimental group. The research sample will be examined in the laboratory. The sample used in this study is a preparation that has been made by dissolving Pb and Hg so that it is like waste from the batik industry or electroplating waste or battery factory waste. The variations in this study were the current / voltage (16, 20, and 24) volts and the detention time (30, 40, 50, and 60) minutes. The independent variable is electrocoagulation which is equipped with cathode and anode. This variable will affect changes in the dependent variable. The dependent variable in this study is the quality of the waste after electrocoagulation by observing the parameters of Pb and Hg. Statistical Analysis: Data analysis using the One-way Anova test or One-way Anova. Results: The results of this study indicate that electrocoagulation as a reducing agent at 16 Volts, 20 Volts, and 24 Volts with a contact time of 30 minutes, 40 minutes, 50 minutes and 60 minutes has a significant effect on Pb and Hg reduction with α = 0.05. The most significant reduction in average Pb occurs in processing with a 20 volt electricity voltage and 60 minutes contact time. Meanwhile, the most significant decrease in Hg levels occurs in processing with a 24 volt electricity voltage and contact time for 30 minutes. Discussion and Conclusion: The reduction in Pb and Hg levels using the electrocoagulation method with aluminum electrodes comes from a redox reaction process where the anode (in acidic pH) will form the Al(s) → Al3+ (aq)¬ + 3e and the cathode will form 3H+ (aq) + 3e- → 1,5H2 (g)¬. After the anode and cathode react, there will be a floc formation which functions as a coagulant that will bind Pb. The conclusion of this study is that the most significant decrease in the average Pb level occurs in processing with a power supply of 20 volts and a contact time of 60 minutes. Meanwhile, the most significant decrease in Hg levels occurred in the treatment with 24 volt electricity and the contact time was 30 minutes. Keywords: Electro-coagulation, Voltage, Contact time, Heavy metals.